A note on mamluk historians' description of plagues in Egypt - Hanif, Md Lateh @ Junid; Noor Inayah, Yaakub; Wan Kamal, Mujani; Wan Mohd Hirwani, Wan Hussain (2011)
The plague which took place during the Mamluk era had big impacts on the economic life in Egypt. This disaster caused high mortality and reduced the agricultural production. It is the aim of this article to analyse the plague which maimed fifty years before the fall of kingdom and how this disaster affected agriculture during that time.